1991
DOI: 10.1111/j.1365-2362.1991.tb01414.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of transferrin receptors by monocytes and peritoneal macrophages from renal failure patients treated by continuous ambulatory peritoneal dialysis (CAPD)

Abstract: Approximately 20% of monocytes and peritoneal macrophages from renal failure patients undergoing continuous ambulatory peritoneal dialysis (CAPD) were transferrin-receptor (TfR) positive by immunofluorescence, whereas cells from normal controls were generally TfR negative, as were monocytes from rheumatoid arthritis patients and from renal failure patients treated by haemodialysis. There was a significant correlation between the length of time on CAPD and the proportion of TfR-positive blood monocytes. CAPD pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1994
1994
2002
2002

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Several authors have reported that PMOs from CAPD patients appear to be in a state of chronic activation (16,17). Other authors have described an increased expression of transferrin receptors on peripheral monocytes and on PMOs from PD patients (18,19). It was stated that, due to the repeated removal of peritoneal cells during dialysis, relatively immature monocytes are constantly invading the peritoneal cavity from the blood.…”
Section: Possible Mechanism For a Lower Incidence Of Peritonitis In Amentioning
confidence: 98%
“…Several authors have reported that PMOs from CAPD patients appear to be in a state of chronic activation (16,17). Other authors have described an increased expression of transferrin receptors on peripheral monocytes and on PMOs from PD patients (18,19). It was stated that, due to the repeated removal of peritoneal cells during dialysis, relatively immature monocytes are constantly invading the peritoneal cavity from the blood.…”
Section: Possible Mechanism For a Lower Incidence Of Peritonitis In Amentioning
confidence: 98%
“…A number of studies indicate that peritoneal macrophages in peritoneal dialysis patients are relatively immature, and that the immaturity becomes more pronounced with time on dialysis (12)(13)(14)(15). They also have an activated phenotype, possibly as a result of exposure to the dialysate (10,16,17).…”
Section: Leukocytes In the Peritoneal Cavitymentioning
confidence: 99%
“…Several researchers have reported that peritoneal macrophages and lymphocytes ap pear to be in a state of chronic activation as evidenced by the enhanced expression of sur face antigens such as HLA-DR. CD25 (the IL-2 receptor), and CD71 (transferrin receptor) [27][28][29]. Theoretically, chronic activation of peritoneal leukocytes could result in chronic production of fibrogcnic cytokines and oxida tive free radicals, which, in turn, could lead to mesothelial cell toxicity and membrane fibro sis [30,31], Bos et al [32] have demonstrated in a rat model that current peritoneal dialysis solutions could induce peritoneal mononu clear cell activation.…”
Section: Dialysate Ph and Phagocytic Cell Functionmentioning
confidence: 99%